Evaluasi Pengelolaan Sediaan Farmasi, Alat Kesehatan, dan Bahan Medis Habis Pakai di Apotek Chrysto Kabupaten Banggai - Wanti, Ris; Nurlina, Nurlina; Aztriana, Aztriana (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
The implementation of pharmaceutical services in pharmacies must guarantee the availability of pharmaceutical preparations, medical devices and consumable medical materials that are safe, of good quality, useful and affordable. Therefore, pharmacists must understand and be aware of the possibility of errors in the management of pharmaceutical preparations, medical devices and consumable medical materials in pharmacies. This study aims to describe and evaluate the management of pharmaceutical preparations, medical devices, and medical consumables at the Chrysto Pharmacy, Banggai Regency. This research is a descriptive study with a qualitative approach using interviews, observation, and document review. The results of the study indicate that there are still several activities that have not been carried out, especially in planning activities that are still not optimal which results in frequent drug stock vacancies. In accordance with the standard regulations in Indonesia, namely the Regulation of the Minister of Health of the Republic of Indonesia Number 73 of 2016 and the 2019 Technical Guidelines for Pharmaceutical Service Standards in Pharmacies, the management of pharmaceutical preparations, medical devices and consumable medical materials at the Chrysto Pharmacy, Banggai Regency is in the good category with a percentage value of 66%.